Učiteljeva literarnodidaktična kompetenca in notranja učna diferenciacija pri pouku književnosti - Kerndl, Milena (Revija za elementarno izobraževanje, 2014)
Teacher’s Literary Didactic Competence and Internal Differentiation in the Literature Classroom. The article presents a pedagogical experiment and its findings. It was carried out as the second part of the research Differentiation and Individualisation in the Literature Classroom in the Third Cycle of Basic School. In the first phase of the research we used quantitative methods, which involved 274 Slovene language teachers and 667 students in order to find out how teachers implemented differentiation and individualisation principles in the literature classroom in smaller (mixed-ability) groups in the third cycle. It turned out that most teachers did not understand the basic principles of differentiation and individualisation and had poor awareness of both students’ reception ability as well as of their horizon of expectations. Due to the fact that the pedagogic syllabus for teacher training does not involve the above mentioned field, the second phase of the research concentrated on the pedagogical experiment, where 30 teachers developed a new literary-didactic competence which later enabled them to perceive/recognize the students’ horizon of expectations related to the students’ literary reception metacognition development. Data were gathered by observation in the classroom, lesson plan analysis, and teachers’ self-evaluation. The basic findings show that teachers should develop this competence and need further training. Without training even additional material (didactic manual) would not yield the desired influence on instruction regarding differentiation and individualisation. In other words, only expert and guided in-service teacher training can lead to modern and learner centred instruction.
Keywords: literature instruction; third cycle of basic school; differentiation/individualisation; teacher‘s literary didactic perception competence which enables teachers to recognize the students‘ horizon of expectations and their development of literature reception metacognition